Positive pole piece of secondary battery and preparation method of positive pole piece

By applying the binder theoretical feeding relationship formula and dry mixing and high-speed shearing technology in the dry electrode process, the preparation process of the positive electrode sheet is optimized, and the influence of the raw material particle state and the degree of binder fibrosis on the electrode performance is solved, and the high-performance preparation of the dry positive electrode sheet is achieved.

CN119764349APending Publication Date: 2025-04-04YANGTZE RIVER DELTA PHYSICS RES CENT CO LTD

Patent Information

Application Number
CN202411956849.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing dry electrode process has difficulties in optimizing the particle state of raw materials and the degree of fibrosis of the binder, resulting in poor electrode performance.

Method used

By optimizing the dry process, using the binder theoretical feeding relationship formula to guide the actual feeding, combining dry mixing and high-speed shearing technology, fibrosis is achieved, high-quality positive electrode dry powder is formed, and dry positive electrode sheets with excellent electrical and mechanical properties are prepared through film formation and rolling thermal composite technology.

Benefits of technology

The dry positive electrode sheet has achieved significant improvements in energy density, conductivity and magnification, and is suitable for the particle state of different electrode materials, improving the overall performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764349A_ABST
    Figure CN119764349A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a positive pole piece of a secondary battery, the positive pole piece is prepared by a dry process, and when process parameters meet the following formula: # imgabs0 # 0.6 * S0 < = S1 < = 1.5 * S0, the prepared positive pole piece has remarkable advantages in the aspects of electrical properties and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dry-process electrodes and secondary batteries, in particular to a secondary battery positive electrode sheet and a dry-process electrode preparation method thereof. Background Art

[0002] Secondary batteries are widely used in various electronic devices and electric vehicles and are one of the most mainstream battery technologies. For example, in mobile phones, portable computers, camcorders, cameras, electric vehicles, energy storage systems and other fields. Despite its wide application, its safety, cycle life and cost still face huge challenges. For example, the existing lithium-ion battery preparation process mostly adopts wet method, which has problems such as solvent residue and environmental pollution. The dry electrode preparation process has become a research hotspot due to its advantages such as solvent-free, environmentally friendly and easy large-scale production. Compared with the traditional wet coating technology, the dry electrode preparation process has the following advantages:

[0003] Simple manufacturing process: There are few manufacturing process steps. After mass production, the manufacturing cost of the battery cell can be reduced by 18%. No solvent NMP is used, which is more environmentally friendly and more suitable for large-scale production. The dry process does not require solvents, reduces the baking and solvent recovery steps in the electrode coating process, and the equipment occupies a smaller area, which is more suitable for large-scale production of electrodes.

[0004] High energy density: Since the wet method requires a solvent, more gaps will be left between the active material and the conductive agent after the solvent evaporates, and the gaps cause the material's compaction density to be low. There is no drying process in the dry method, so there are no gaps left after the solvent evaporates, and the contact between the particles is closer. Dry electrodes can achieve a higher compaction density. Since they contain more active substances per unit volume, dry electrodes also have the technical path to achieve a higher energy density. Under the same conditions, the energy density of dry electrodes can be increased by 20%. At the same time, the thickness limit of dry electrodes is larger, which can increase the surface capacity.

[0005] Wide range of applications: The dry electrode process is suitable for a variety of battery types, including lithium-ion batteries, solid-state batteries, etc., and can be applied to different electrode materials, such as positive electrode materials, negative electrode materials, etc.

[0006] Although dry electrode technology has shown significant advantages in battery manufacturing, there are still many challenges, such as the immaturity of application-end formulations and fibrillation processes. The final performance of dry electrodes is affected by the degree of binder fibrillation and the state of different raw material particles (particle size, distribution, proportion, specific surface area, etc.). How to obtain more optimized process conditions for different electrode raw material particle states to achieve better performance of dry electrodes is one of the key technical issues that need to be urgently solved in the dry process. Summary of the invention

[0007] In view of the above problems in the prior art, the present invention provides a secondary battery positive electrode sheet and a preparation method thereof. The positive electrode sheet prepared by an optimized dry process has significant advantages in both electrical and mechanical properties.

[0008] The present invention first provides a method for preparing a positive electrode sheet of a secondary battery, comprising the following steps:

[0009] The positive electrode raw materials containing positive electrode active materials, binders and conductive agents are sequentially subjected to dry mixing and high-speed shearing to achieve fibrillation to form positive electrode dry powder, the positive electrode dry powder is prepared into positive electrode membrane using a film forming device, and the positive electrode membrane and positive electrode foil are then hot-compounded by roller pressing to obtain dry-process positive electrode sheets;

[0010] In the above steps, the process parameters satisfy the following formula

[0011]

[0012] 0.6*S0≤S1≤1.5*S0, preferably, 0.7*S0≤S1≤0.9*S0,

[0013] Among them, S0 is the theoretical mass proportion of the binder in the positive electrode raw material, S1 is the actual mass proportion of the binder in the positive electrode raw material, D5, D 50 , D 99 are the cumulative distribution particle sizes of the positive electrode active materials at 5%, 50% and 99%, respectively, in μm, Z is the mass proportion of the positive electrode active material in the positive electrode raw material, and X is the specific surface area of ​​the positive electrode active material, in m 2 / g, Y is the number average molecular weight of the binder, C1 is the degree of fibrillation of the binder after high-speed shearing, with complete fibrillation as 100%, K1 and K2 are empirical coefficients, and K1=5 and K2=1 respectively.

[0014] As some further preferred embodiments, the positive electrode active material of the present invention adopts a lithium battery positive electrode active material or a sodium battery positive electrode active material, preferably a lithium battery positive electrode active material; the lithium battery positive electrode active material is selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium titanate, etc.; the sodium battery positive electrode active material is selected from transition metal oxides such as O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, polyanion compounds such as sodium vanadium phosphate (Na3V2(PO4)3), Prussian blue compounds such as Fe4[Fe(CN)6]3.

[0015] As some further preferred embodiments, the adhesive of the present invention is selected from one or more of fluorine-containing polymers, polyamides, and SBR.

[0016] As some further preferred embodiments, the conductive agent of the present invention is selected from one or more of SP, carbon nanotubes, VGCF, KS-6, KS-15, Ketjen black, graphene, and acetylene black.

[0017] As some further preferred schemes, the mass proportions of positive electrode active material, binder and conductive agent in the positive electrode raw material range from 80% to 98%, 1% to 10% and 0.5% to 8%.

[0018] As some further preferred solutions, the stirring rate of the dry mixing is 1000-3000 rpm; further preferably, the temperature of the dry mixing is 16-25° C., and the time is 5-120 min.

[0019] As some further preferred schemes, the shear rate of high-speed shearing is 4000-8000 rpm, and the fiberization temperature of high-speed shearing is 50-150° C.; further preferably, the time is 3-60 min.

[0020] As some further preferred schemes, the fibrillation degree C1 of the adhesive after high-speed shearing is preferably above 80%, preferably above 85%, above 90%, and above 95% respectively; among the fibrillation degrees, complete fibrillation C1=100% is used as a normalized benchmark.

[0021] As some further preferred schemes, the high-speed shearing also includes a process of obtaining positive electrode dry powder by refining the material.

[0022] As some further preferred schemes, when the positive electrode dry powder is formed into a film, the film thinning temperature is 70-300°C.

[0023] As some further preferred schemes, the rolling pressure of the rolling hot compounding is 1-50t and the temperature is 70-300°C.

[0024] The present invention also provides a secondary battery positive electrode sheet and a battery obtained by the above method. The negative electrode in the battery is not limited and can be obtained by assembling a known negative electrode with the secondary battery positive electrode sheet of the present invention.

[0025] Compared with the prior art, the present invention has at least the following beneficial effects:

[0026] By considering the relationship between different states of electrode raw material particles and the degree of fiberization of the binder during the dry process, a theoretical feed relationship formula for the binder was proposed for the first time. Based on the theoretical feed relationship formula as a guide for actual feed, a feasible solution for the actual feed mass proportion of the binder in the positive electrode raw material during dry process preparation was provided, and the optimal process conditions for the dry positive electrode under different raw material particle states were successfully obtained. The dry positive electrode prepared by the method of the present invention has good electrical properties and has significant advantages in energy density, conductivity and rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 The figure is a comparison of the rate tests of Example 1-1 of the present invention and Comparative Examples 1-3.

[0029] Figure 2 This is the SEM of the dry electrode obtained in Example 1-1 of the present invention.

[0030] Figure 3 These are the performance test results of the positive electrode sheets obtained from Example 1-1 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0031] Detailed preparation methods and technical steps are provided in the embodiments of the present invention, and are intended to fully illustrate the specific implementation process of the present invention. However, these detailed technical details only represent a specific way to realize the present invention, and are not intended to limit the core content of the present invention or its protection scope. It should be understood by those skilled in the art that these embodiments are only for illustrative purposes and should not be regarded as limiting the only or exclusive implementation mode of the present invention.

[0032] In a first aspect, the present invention first provides a method for preparing a positive electrode sheet of a secondary battery, comprising the following steps:

[0033] The positive electrode raw materials containing positive electrode active materials, binders and conductive agents are sequentially subjected to dry mixing and high-speed shearing to achieve fibrillation to form positive electrode dry powder, the positive electrode dry powder is prepared into positive electrode membrane using a film forming device, and the positive electrode membrane and positive electrode foil are then hot-compounded by roller pressing to obtain dry-process positive electrode sheets;

[0034] In the above steps, the process parameters satisfy the following formula

[0035]

[0036] 0.6*S0≤S1≤1.5*S0, preferably, 0.7*S0≤S1≤0.9*S0

[0037] Among them, S0 is the theoretical mass proportion of the binder in the positive electrode raw material, S1 is the actual mass proportion of the binder in the positive electrode raw material, D5, D 50 , D 99 are the cumulative distribution particle sizes of the positive electrode active materials at 5%, 50% and 99%, respectively, in μm, Z is the mass proportion of the positive electrode active material in the positive electrode raw material, and X is the specific surface area of ​​the positive electrode active material, in m 2 / g, Y is the number average molecular weight of the binder, C1 is the degree of fibrillation of the binder after high-speed shearing, with complete fibrillation as 100%, K1 and K2 are empirical coefficients, and in the present invention, K1=5 and K2=1 respectively.

[0038] In the process of dry electrode preparation, the final effect of electrode film formation is mainly improved by promoting the fiberization of the binder. At the macro level, the fiberization degree has a more important correlation with the state of the raw material particles. Therefore, the applicant has considered selecting the above D5 and D 50 , D 99 , Z, X, Y as the key parameters of the raw material particle state and the fibrillation degree C1 as the synergistic correlation factor, explore their influence on the theoretical feed of the binder, confirm the empirical parameters K1 and K2 that compound the above influence relationship, and obtain the binder theoretical feed relationship formula (the above formula (1)). This formula takes the raw material mass proportion as the central basis, takes into account the cross-influence of particle size and distribution on specific surface area in the state of positive electrode raw material particles, and synergistically considers the interaction of this influence with the molecular weight and fibrillation degree of the binder, provides a reliable basis for the theoretical feed proportion of the binder, and then further provides a feasible solution for the actual feed mass proportion of the binder in the positive electrode raw material through the actual empirical relationship between the theoretical feed and the actual feed. Therefore, through the above formula relationship of the present invention, the optimal process conditions for the dry-process positive electrode under different raw material particle states can be effectively obtained, providing reliable guidance for selecting suitable binders and their feed amounts.

[0039] In order to more accurately obtain process parameters that satisfy the above relationship, those skilled in the art may select target conditions within the existing general dry process condition range, which is helpful to eliminate other interferences under non-general conditions.

[0040] As some examples, the secondary battery of the present invention can be applied to lithium batteries and sodium batteries, and the positive electrode active material can also be one of the known positive electrode materials of lithium batteries or sodium batteries. As some illustrative examples, the positive electrode active material in the lithium battery can be selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium titanate, etc.; the positive electrode active material in the sodium battery can be selected from transition metal oxides such as O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, polyanion compounds such as sodium vanadium phosphate (Na3V2(PO4)3), Prussian blue compounds such as Fe4[Fe(CN)6]3, etc. One or more.

[0041] As some examples, the adhesive of the present invention can be selected from one or more of fluoropolymers, polyamides, SBR, etc., preferably fluoropolymers, such as one or more of polyvinylidene fluoride-hexafluoropropylene copolymers, PTFE and PVDF-HFP. The high bond energy of the CF bond is beneficial to improving the stability and corrosion resistance of the main chain skeleton, and is also beneficial to combining with conductive ions to improve the ion conductivity.

[0042] As some examples, the conductive agent of the present invention can be selected from one or more of SP, carbon nanotubes, VGCF, KS-6, KS-15, Ketjen black, graphene, and acetylene black. The combination of linear conductive agents and point conductive agents is more conducive to the establishment and function of a conductive network.

[0043] As some examples, the mass proportions of positive electrode active material, binder and conductive agent in the positive electrode raw material are preferably in the range of 80% to 98%, 1% to 10% and 0.5% to 8% respectively. The optimized proportion range is beneficial to improving the overall energy density of the dry electrode.

[0044] As some examples, the stirring rate of dry mixing can be 1000-3000 rpm, and can be further carried out at 16-25° C. to improve the stirring efficiency. The stirring time is preferably 5-120 min.

[0045] As some examples, the shear rate of high-speed shearing can be 4000-8000 rpm, the fiberization temperature of high-speed shearing can be set to 50-150° C., and the time is preferably 3-60 min.

[0046] As some examples, the fibrillation degree C1 of the adhesive after high-speed shearing is preferably 80% or more, preferably 85%, 90%, and 95% or more, respectively. The detection method of the fibrillation degree is not limited, and can be carried out by known methods, such as by specific surface area change method (CN118299498A), crystallinity change method (KR102661426B1), color difference ratio change method of two-dimensional image (CN118837354A), etc. Further, for the purpose of convenience or unification of judgment, the fiberization level of the correlation curve established in different fiberization degree detection methods when reaching the limit state of the curve (∞ or limit) can also be used as the normalized benchmark of the complete fiberization C1=100% of the present invention, and the correlation curve is a correlation curve established between the fiberization degree indicators detected by different methods relative to the evaluation index parameters (specific surface area, crystallinity, color difference ratio).

[0047] As some examples, after high-speed shearing, the process of obtaining positive electrode dry powder by refining the material is also included. Refining is conducive to obtaining fine and uniform dry powder material.

[0048] As some examples, when the positive electrode dry powder is formed into a film, the film thinning is carried out at a temperature of 70-300°C.

[0049] As some examples, the roll pressure of the roll hot compounding can be set to 1-50t, and the temperature can be set to 70-300°C.

[0050] Suitable film thinning and roller pressing thermal composite conditions are conducive to improving the film forming efficiency, obtaining positive electrode sheets with designed target thickness, surface density and porosity, and improving the overall mechanical properties of the sheets.

[0051] The following is an explanation of the specific implementation cases.

[0052] Case Group 1

[0053] Example 1-1

[0054] The lithium iron phosphate positive electrode active material, conductive agent SP, conductive agent carbon nanotubes, conductive agent acetylene black, and binder PTFE were mixed in a mass ratio of 95:1.5:0.5:0.5:2.5, and mixed evenly in a dry mixing mixer under solvent-free conditions at a speed of 3000 rpm for 5 minutes, and high-speed shear fibrillation at a speed of 4000 rpm for 10 minutes to achieve a fibrillation degree C1 = 100%, forming a positive electrode dry powder. Among them, the particle size distribution of the lithium iron phosphate positive electrode active material is D 50 =1.32μm, D5=0.38μm, D 99 =11.62μm, specific surface area is X = 11.42m 2 / g, the number average molecular weight Y of PTFE is about 5 million.

[0055] The positive electrode dry powder was pressed into a film using a film thinning device. The film forming roller temperature was 150°C, the initial film thickness was 180 μm, and the surface density was 30 mg / cm 2 , to ensure smooth film formation. The initial film is thinned several times using film thinning equipment until the film reaches a surface density of 20mg / cm 2 The positive electrode film is rolled into two rolls for roller pressing and hot compounding.

[0056] The positive electrode film was heat-compounded by roller pressing using a heat-compounding device. The roller temperature was 100°C and the pressure was 10T. The positive electrode film was heat-compounded on both sides of the 12μm carbon-coated aluminum foil. After winding, the positive electrode film was roll-pressed to obtain a positive electrode film with a double-sided surface density of 40mg / cm 2 .

[0057] The graphite negative electrode material, conductive agent SP, binder CMC, and binder SBR were mixed in a mass ratio of 95:2.2:1.3:1.5, and slurried with deionized water solvent. After the slurry was prepared, it was wet-coated on the surface of 6μm copper foil, and the double-sided surface density was 16mg / cm 2 The coated graphite negative electrode sheet is rolled and the compaction density is 1.6g / cm 3 .

[0058] The positive electrode sheet and the negative electrode sheet prepared above are made into soft-pack batteries according to the general process for subsequent performance testing.

[0059] Example 1-2

[0060] The soft-pack battery cell was prepared by the same method as in Example 1-1, except that the conductive agent was replaced with SP, the roller temperature in roller hot compounding was 120° C., and the pressure was 5T.

[0061] Examples 1-3

[0062] The soft-pack battery cell is prepared by the same method as in Example 1-1, except that the lithium iron phosphate positive electrode active material, the conductive agent, and the binder are mixed in a ratio of approximately 95:3.99:1.01 (approximately 95:4:1) by mass, and the compounding ratio of the three conductive agents is the same as in Example 1-1.

[0063] Comparative Examples 1-1, 1-2

[0064] The soft-pack battery cell was prepared by the same method as in Example 1-1, except that the mass ratios of the lithium iron phosphate positive electrode active material, the conductive agent, and the binder were changed for mixing, wherein the compounding ratios of the three conductive agents were the same as in Example 1-1. The mass ratios of the mixed materials are listed in Table 1.

[0065] Comparative Examples 1-3

[0066] The positive electrode sheet was prepared by a conventional wet method using the same raw materials and proportions as in Example 1-1, and a soft-pack battery cell was assembled with the negative electrode sheet prepared by the same method as in Example 1-1.

[0067] Case Group 2

[0068] Example 2-1

[0069] The soft-pack battery cell was prepared by the same method as in Example 1-1, except that the positive electrode active material was replaced with lithium nickel cobalt manganese oxide with different particle distributions, and the mass ratios of the positive electrode active material, the conductive agent, and the binder were changed, wherein the compounding ratios of the three conductive agents were the same as in Example 1-1.

[0070] Example 2-2

[0071] The soft-pack battery cell was prepared by the same method as in Example 2-1, except that the mass proportions of the positive electrode active material, the conductive agent, and the binder were changed.

[0072] Comparative Example 2-1

[0073] The soft-pack battery cell was prepared by the same method as in Example 2-1, except that the mass proportions of the positive electrode active material, the conductive agent, and the binder were changed.

[0074] Case Group 3

[0075] Example 3-1

[0076] The soft-pack battery cell was prepared by the same method as in Example 1-1, except that the adhesive was replaced by PVDF having a number average molecular weight of about 9 million, and the mass proportions of the positive electrode active material, the conductive agent, and the binder were changed. The compounding ratio of the three conductive agents was the same as in Example 1-1, and the high-speed shear rate and time were changed, and the degree of fiberization was controlled to be about 95%.

[0077] Example 3-2

[0078] The soft-pack battery cell was prepared by the same method as in Example 3-1, except that the mass ratios of the positive electrode active material, the conductive agent, and the binder were changed.

[0079] Comparative Example 3-1

[0080] The soft-pack battery cell was prepared by the same method as in Example 3-1, except that the mass ratios of the positive electrode active material, the conductive agent, and the binder were changed.

[0081] The preparation conditions of the above embodiments and comparative examples are listed in Table 1.

[0082] Table 1

[0083]

[0084]

[0085] The cells successfully obtained in the above examples and comparative examples were subjected to rate tests, and were charged at 0.1C in a 25°C incubator, and were discharged at 0.1C / 0.2C / 0.33C / 0.5C rates. The test results are shown in Tables 2 and 3. Figure 1 .

[0086] Table 2

[0087] Dry production 0.1CDC 0.2CDC 0.33CDC 1CDC Example 1-1 success 100% 99.16% 98.52% 95.44% Example 1-2 success 100% 98.08% 96.25% 91.33% Examples 1-3 success 100% 97.01% 95.26% 88.25% Comparative Example 1-1 fail / / / / Comparative Example 1-2 success 100% 93.67% 91.33% 84.49% Comparative Examples 1-3 success 100% 96.41% 93.87% 85.63% Example 2-1 success 100% 99.03% 98.15% 94.88% Example 2-2 success 100% 97.97% 95.75% 92.81% Comparative Example 2-1 success 100% 95.76% 94.06% 85.22% Example 3-1 success 100% 98.75% 97.64% 94.57% Example 3-2 success 100% 97.61% 95.82% 92.30% Comparative Example 3-1 fail / / / /

[0088] It can be seen from the results of the above three case groups that a dry-process positive electrode with good electrical properties can be successfully obtained through the dry process of the present invention. Each case group targets a raw material state system in different conditions, and it can be seen that the formula relationship of the present invention is universal. In case group 1, comparative examples 1-1 and 1-2 adopted actual feed ratios that were not suitable for the theoretical feed guidance ratio of the present invention, resulting in the failure to successfully prepare a dry-process positive electrode by a dry method in comparative example 1-1. At the same time, although comparative example 1-2 successfully prepared a dry-process positive electrode, the rate performance was greatly reduced. Comparative example 1-3 uses a conventional wet process, and it can be seen that the rate performance has not been improved. Figure 1 The rate test comparison between Example 1-1 and Comparative Examples 1-3 is shown, and it can be clearly seen that the dry electrode of the present invention after optimizing the conditions through the formula has significant advantages in rate discharge. Figure 2 The SEM of the dry electrode obtained in Example 1-1 of the present invention is shown, and it can be seen that the positive electrode material has formed a uniform and compact dispersion state, which is conducive to the good performance of the positive electrode electrical performance. Case Group 2 and Case Group 3 also show that the actual feed ratio that is not suitable for the theoretical feed ratio of the present invention is used in the comparative example, which will lead to the failure of the electrode preparation or the difficulty in effectively improving the electrical performance.

[0089] By comparing the embodiments in the above case groups, it can be seen that the theoretical mass proportion S0 of the binder in the positive electrode raw material confirmed by the formula relationship of the present invention is used as a guiding parameter for the actual feed proportion S1 of the binder, and the actual feed proportion S1 can be further optimized according to S0. As shown in the embodiments, the discharge capacity of the embodiments of the present invention at low rate (0.33C DC) can reach ≥95%, and the discharge capacity at high rate (1C DC) can reach ≥85%; and further when 0.7*S0≤S1≤0.9*S0, the high rate can be further improved, and the discharge capacity at high rate (1C DC) can reach ≥90%.

[0090] The positive electrode plates obtained in Example 1-1 and Comparative Examples 1-3 were further tested for their performance, as shown in Table 3 and Figure 3 As shown, it can be seen that the positive electrode sheet obtained by the method of the present invention has achieved a synergistic improvement in mechanical properties and electrical properties.

[0091] Table 3

[0092] serial number <![CDATA[Compaction density / g / cm 3 > Resistivity / Ω*cm Peel strength / N / m Example 1-1 2.5 7.2 61.84 Comparative Examples 1-3 2.3 15.49 29.45

[0093] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A method for preparing a positive electrode sheet of a secondary battery, comprising the following steps: The positive electrode raw materials containing positive electrode active materials, binders and conductive agents are sequentially subjected to dry mixing and high-speed shearing to achieve fibrillation to form positive electrode dry powder, the positive electrode dry powder is prepared into positive electrode membrane using a film forming device, and the positive electrode membrane and positive electrode foil are then hot-compounded by roller pressing to obtain dry-process positive electrode sheets; In the above steps, the process parameters satisfy the following formula 0.6*S0≤S1≤1.5*S0, preferably, 0.7*S0≤S1≤0.9*S0, in, S0 is the theoretical weight ratio of the binder in the positive electrode raw material, S1 is the actual weight ratio of the binder in the positive electrode raw material, D5, D 50 , D 99 are the cumulative distribution particle sizes of the positive electrode active materials at 5%, 50% and 99%, respectively, in μm, Z is the mass proportion of the positive electrode active material in the positive electrode raw material, and X is the specific surface area of ​​the positive electrode active material, in m 2 / g, Y is the number average molecular weight of the binder, C1 is the degree of fibrillation of the binder after high-speed shearing, with complete fibrillation as 100%, K1 and K2 are empirical coefficients, and K1=5 and K2=1 respectively.

2. The method for preparing a positive electrode sheet of a secondary battery according to claim 1, characterized in that: The positive electrode active material is a lithium battery positive electrode active material or a sodium battery positive electrode active material, preferably a lithium battery positive electrode active material; the lithium battery positive electrode active material is selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium titanate, etc.; the sodium battery positive electrode active material is selected from transition metal oxides such as O3-NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, polyanion compounds such as sodium vanadium phosphate (Na3V2(PO4)3), Prussian blue compounds such as Fe4[Fe(CN)6]3; The adhesive is selected from one or more of fluoropolymer, polyamide and SBR; The conductive agent is selected from one or more of SP, carbon nanotubes, VGCF, KS-6, KS-15, Ketjen black, graphene, and acetylene black.

3. The method for preparing a positive electrode sheet of a secondary battery according to claim 1, characterized in that: The mass proportions of positive electrode active material, binder and conductive agent in the positive electrode raw materials range from 80% to 98%, 1% to 10% and 0.5% to 8%.

4. The method for preparing a positive electrode sheet of a secondary battery according to claim 1, characterized in that: The stirring rate of the dry mixing is 1000-3000 rpm; more preferably, the temperature of the dry mixing is 16-25° C., and the time is 5-120 min.

5. The method for preparing a positive electrode sheet of a secondary battery according to claim 1, characterized in that: The shear rate of high-speed shearing is 4000-8000 rpm, and the fiberization temperature of high-speed shearing is 50-150° C.; more preferably, the time is 3-60 min.

6. The method for preparing a positive electrode sheet for a secondary battery according to claim 1, characterized in that: The fibrillation degree C1 of the adhesive after high-speed shearing is preferably above 80%, preferably above 85%, above 90%, and above 95% in that order; among the fibrillation degrees, complete fibrillation C1=100% is used as a normalized standard.

7. The method for preparing a positive electrode sheet for a secondary battery according to claim 1, characterized in that: After high-speed shearing, the process also includes obtaining positive electrode dry powder by refining the material.

8. The method for preparing a positive electrode sheet for a secondary battery according to claim 1, characterized in that: When the positive electrode dry powder is formed into a film, the film thinning temperature is 70-300°C.

9. The method for preparing a positive electrode sheet for a secondary battery according to claim 1, characterized in that: The roller pressing pressure of roller hot compounding is 1-50t and the temperature is 70-300℃.

10. A secondary battery positive electrode sheet obtained by the method according to any one of claims 1 to 9, and a battery comprising the positive electrode sheet.

Citation Information

Patent Citations

  • Dry-method electrode diaphragm and method for detecting fibrosis degree of binder in dry-method electrode diaphragm

    CN118299498A

  • Method for monitoring fibrosis degree in dry-method membrane preparation process

    CN118837354A

  • ELECTRODE FOR electrochemical devise comprising Dry electrode film and method for MANUFACTURING the same

    KR102661426B1

  • Positive electrode material, preparation method and application thereof, and lithium ion battery

    CN115832231A

  • Safety coating composition, positive plate, secondary battery and electronic equipment

    CN116111096A

Cited By

  • Dry-method negative electrode, preparation method thereof and battery

    CN120497283A

  • Dry-method positive electrode, preparation method thereof and battery

    CN120497284A

  • A dry-method cathode, a preparation method thereof, and a battery

    CN120497284B

  • Dry-method solid electrolyte layer for battery, preparation method of dry-method solid electrolyte layer and solid-state battery

    CN120511349A

  • A dry-method solid electrolyte layer for a battery, a method of manufacturing the same, and a solid-state battery

    CN120511349B